Dissection of intercostal nerves by means of assisted video thoracoscopy: experimental study - Cáceres, Juan Pablo; Palazzi, Santos; Palazzi, Jose Luis; Llusá, Manuel; Sanz, M; Varci, S (Journal of Brachial Plexus and Peripheral Nerve Injury, 2013)
In total brachial plexus preganglionic lesions (C5-C6-C7-C8 and T1) different extraplexual neurotizations are indicated for partial motor function restitution. Mostly for the flexion of the elbow. Neurotization with intercostal nerves (ICN) to musculocutaneous nerve has been known and accepted during many years with different results 2 - 5. The customary technique as described by various authors is carried out by means of a large submammary incision to harvest three or four intercostal nerves (Figure 1). Then are connected by direct suture or grafts to the musculocutaneous nerve or its motor branches 6 - 7. In this article the authors described the possibility of dissection intercostal nerves by means of assisted video thoracoscopy. (VATS-videdo assisted thoracic surgery).